1993
DOI: 10.1210/jcem.76.3.8445028
|View full text |Cite
|
Sign up to set email alerts
|

The role of progesterone in regulating human granulosa cell proliferation and differentiation in vitro.

Abstract: To further elucidate the role of progesterone in regulating granulosa cell function, human granulosa and luteal cells were obtained from follicular aspirates of women undergoing in vitro fertilization and placed in culture. Cells plated at 5 x 10(3) cells/mL doubled after 3 days. In contrast, cells plated at 50 x 10(3) cells/mL did not proliferate, but differentiated, secreting high levels of progesterone. Cells plated at 5 x 10(3) cells/mL and cultured with spent medium from cells plated at 50 x 10(3) cells/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In further confirmation of an autocrine signaling mechanism, we demonstrate that inhibition of the synthesis of progesterone with AMG, a p450scc inhibitor, prevents NRC proliferation. A number of studies have shown that progesterone has previously been shown to regulate proliferation and protect cells from apoptosis in autocrine/paracrine mechanisms (15,47,55). Since cholangiocyte secretion of progesterone is downregulated by BDL, serum levels of progesterone (which are considerably elevated in serum compared with cholangiocyte supernatants) indicate that the paracrine signaling mechanism may play a role during cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…In further confirmation of an autocrine signaling mechanism, we demonstrate that inhibition of the synthesis of progesterone with AMG, a p450scc inhibitor, prevents NRC proliferation. A number of studies have shown that progesterone has previously been shown to regulate proliferation and protect cells from apoptosis in autocrine/paracrine mechanisms (15,47,55). Since cholangiocyte secretion of progesterone is downregulated by BDL, serum levels of progesterone (which are considerably elevated in serum compared with cholangiocyte supernatants) indicate that the paracrine signaling mechanism may play a role during cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…The LH surge not only induces ovulation but also stimulates GCs of the preovulatory follicle to luteinize which results in transformation of the follicle in the corpus luteum. It appears that LH surge acts as a "switch", preventing cell proliferation and initiating luteinization, as evidenced by enhanced progesterone synthesis (8). It should be stressed that GCs were harvested closely before ovulation from corona radiata and a part of cumulus oophorus of hormonally stimulated women.…”
Section: Discussionmentioning
confidence: 99%
“…This nonsurgical, reversible method of LH ablation and replacement will allow further studies examining the role of LH in the regulation of specific structural and functional properties of the primate corpus luteum. Studies supporting a role for progesterone in the regulation of luteal structure (8), pro-gesterone production (8,44), and LH receptor expression (9) could be advanced by using this model in conjunction with steroid synthesis inhibitors (8) to further elucidate the role of progesterone in the regulation of the structure and functional life span of the corpus luteum in an environment of sustained gonadotropin support.…”
Section: Discussionmentioning
confidence: 99%